Newnes electrical power engineer's handbook - Warne, D. F. (Oxford : Newnes, 2005)
The second edition of this popular engineering reference book, previously titles Newnes Electrical Engineers Handbook, provides a basic understanding of the underlying theory and operation of the major classes of electrical equipment. With coverage including the key principles of electrical engineering and the design and operation of electrical equipment, the book uses clear descriptions and logical presentation of data to explain electrical power and its applications. Each chapter is written by leading professionals and academics, and many sections conclude with a summary of key standards. The new edition is updated in line with recent advances in EMC, power quality and the structure and operation of power systems, making Newnes Electrical Power Engineers Handbook an invaluable guide for todays electrical power engineer. A unique, concise reference book with contributions from eminent professionals in the field Provides straightforward and practical explanations, plus key information needed by engineers on a day-to-day basis Includes a summary of key standards at the end of each chapter.
Introduction. -- Principles of Electrical Engineering. -- Materials for Electrical Engineering. -- Measurement and Instrumentation. -- Generators. -- Transformers. -- Switchgear. -- Fuses and protection relays. -- Wires and cables. -- Motors, motor control and drives. -- Power Electronic Converters. -- Batteries and fuel cells. -- The Power System. -- Power Quality and EMC. -- Electricity & potentially explosive atmospheres. -- Principles of Electrical Safety. -- Index.
Previous ed. published as: Newnes electrical engineer's handbook. 2000.
Includes bibliographical references and index.
Keywords: Electrical engineering -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc